Emergency Department Patient Satisfaction Survey in a Tertiary Care Hospital of Eastern Nepal - Poudel, Masum; Bhandari, Rabin; Uprety, Samyog; Chaudhary, Ritesh; Yadav, Ashok (Journal of BP Koirala Institute of Health Sciences, 2023)
Background: Patient satisfaction is one of the most important indicators of the quality of emergency care. This hospital-based cross-sectional study was performed to assess patient satisfaction in the Emergency department of a tertiary care hospital and identify the factors associated.Methods: The study was performed on 785 patients visiting Emergency department. Variables under study were satisfaction level, triage score, waiting times, and socio-demographic characteristics. Satisfaction level was measured using a 5-point Likert scale, Cronbach’s alpha (α= 0.86 overall, inter-item α = 0.842-0.859). A score of 47 and above was cut off to denote satisfaction with a sensitivity of 75% and specificity of 81%. Descriptive analysis and Chi-square test was performed to see the association of variables of interests with patient satisfaction. A p-value